The analysis of technical movement of the shooting in water polo - Napolitano, S.; Rosa, R.; Cusano, P. (Sport Science - International Scientific Journal of Kinesiology, 2019)
Introduction: Among the various team sports water polo is a sport suited to the development of motor skills in their technical, space and rules of the game where the time of analysis, evaluation, processing and execution is limited compared to other team sports and may be particularly suitable in the period 9-10 years to acquire the specific techniques of the game. Aim: The aim is to evaluate the effects of motor imagery practice in training. The motor imagery is a cognitive process of mental simulation of actions in absence of movement. There are two methods to improve skills learning through motor imagery: in first person and In third person. The biological basis on which the motor imagery theory is founded, is formed by: mirror neurons. Methods: It is an experimental approach and it consists of two steps. Both groups were videotaped in the execution of sport skills and evaluated, through a check list made by water polo indicators: positioning phase, counter-movement, movement of shooting in 4 level of descriptors by technicians every four months. A sample of water polo team of children ( 9-10 years old) splitting in control and experimental groups, after a pre-assessment, performed by technicians, about technical skills through an evaluation grid prepared "ad hoc" on technical fundamentals taken into the study to form two homogeneous groups (Experimental group n = 10, control group n = 10). Experimental group using modeling video performed by a athletes of National Italian water polo Team could lead to significant changes in technical skills. Results: Data recruit at starting, ongoing and final training program and their analysis, evaluation and comparison by control group show percentage of 9% better outcomes. particularly, at final training shows a minimum improvement 3.2% than ongoing phase that gives a maximum improvement 9.6%, while a substantial balance in the control group with a medium improvement of 3.2% in every phase of training program. Discussion: In this study two basic aspects of the performance are examined: the motor execution and the motor imagine. Both share the same neuro-motor mechanism: the motor imagery. Concerning the water polo it can be useful during the training and the race. So providing the athletes and trainers of a means which uses the motor imagery as a possible application for the improvement of the performance. Conclusions: So in conclusion, the study aims to provide a standard training feasible on a large scale to train the cognitive and physical abilities of an athlete and provide a support tool in the race in order to improve performance, optimize time and to reduce the margin of error.